Decision Support System for Best Lecturer Selection using Analytical Network Process (ANP) and TOPSIS Method - Junita Cahyati Sinaga; Alyauma Hajjah (Institut Bisnis dan Teknologi Pelita Indonesia, 2020)
Lecturer performance is influential in increasing student learning motivation. Each lecturer has a different character, nature and way of teaching. This causes students to choose and determine the best lecturer according to the students themselves. One of the Decision Support Systems (DSS) in assessing the best lecturers is using the ANP and TOPSIS methods. The Analytic Network Process (ANP) method is used to determine the weight of the criteria according to decision making, then the TOPSIS method is used to determine the rank / achievement of lecturers. This decision support system is expected to help and provide an alternative in assessing lecturer achievement. The results of this study will be in the form of an information system which is expected to assist in processing data by designing the best lecturer assessment information system using the ANP and TOPSIS methods.